Comparative efficacy and safety of co-amoxiclav, cefpodoxime proxetil, and levofloxacin in patients with acute uncomplicated bacterial tonsillitis: A prospective, open-label, parallel group study - Suja Xaviar; K. Girish; B. Jagannath; Saibal Das; Probin Joseph (Journal of Family Medicine and Primary Care)
Background: No clinical trials have compared the efficacy and safety of beta-lactam antibiotics and fluoroquinolones in acute uncomplicated bacterial tonsillitis. This study aimed to compare the efficacy and safety of co-amoxiclav (amoxicillin/clavulanic acid), cefpodoxime proxetil, and levofloxacin monotherapy in patients with acute uncomplicated bacterial tonsillitis. Methods: This was a prospective, open-label, parallel-group study where 90 patients with acute uncomplicated bacterial tonsillitis were equally divided into three groups to receive either tablet co-amoxiclav 625 mg thrice daily, tablet cefpodoxime proxetil 200 mg twice daily, or tablet levofloxacin 500 mg once daily for five days. The efficacy was assessed by subjective clinical improvement and objective bacteriological cure at the end of treatment. Safety was assessed by monitoring adverse events during the study period. Results: Co-amoxiclav, cefpodoxime proxetil, and levofloxacin showed comparable clinical responses on days three and seven; however, on day five, levofloxacin showed a significantly reduced cure rate, but a higher improvement rate, than co-amoxiclav and cefpodoxime proxetil. Bacteriologically, the responses were similar in all three groups at week 1. All drugs were well tolerated with a few self-limiting adverse effects. Conclusions: Co-amoxiclav, cefpodoxime proxetil, and levofloxacin showed a comparable clinical and bacteriological cure in acute uncomplicated bacterial tonsillitis and showed a good safety profile.